Condicionantes climáticos e socioeconômicos na espacialização da dengue em período epidêmico e pós-epidêmico na cidade de Fortaleza-CE - Gledson Bezerra Magalhães; Maria Elisa Zanella; Ana Paula Santana; Ricardo Almendra (Confins)
The article analyses the spatial-temporal distribution of dengue in the epidemic year of 2012 and the post-epidemic year of 2013, in the city of Fortaleza-Ceará. For this, were used Kernel maps and geostatistical procedures (Pearson correlation, Cronbach's alpha coefficient, global and local Moran index). Climatologic, epidemiologic and socioeconomic data were collected. In both episodes daily air temperature averages presented ideal conditions for the Aedes Aegypti reproduction with maximum temperature between 30 and 32°C and minimum between 21 and 25 ° C and relative air humidity from 76 to 95%. Between 2012 and 2013, the dengue virus increased its epidemic potential, from an explosive epidemic that evolved, in a short period of time, to an endemic cycle which resulted in the reduction of cases in 2013. In the 2012 episode, the cases of dengue began and spread quickly in the Western part of the city and at specific points in the Southeast region, predominating in those regions in 2013. Correlations statistically indicates the association between dengue incidence and socioeconomic variables.The spatialization of these variables showed that the first cases of the episode of 2013 were registered in the neighborhood that had the worst socioeconomic and/or sanitation conditions.